Masalah-Masalah yang Dialami Anak TK Menurut Guru dan Orangtua - Syahniar Syahniar (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2004)
This study was aimed at describing the problems faced by kindergarten students as seen by teachers and parents The data were collected from 12 kindergarten teachers and 245 parents, selected using the cluster random sampling technique, by using questionnaires. In addition, interviews were done with teachers. The results indicated that there were five problems faced by kindergarten students: social, emotional, moral, understanding-development, and language. The findings imply that role playing, modeling, and group guidance be implemented by kindergarten teachers in counseling processes.